Anders Zorn og Nordisk Samtidskunst. (Ishoj : Arken Museum for Moderne Kunst Ishoj, 2004)
Zorn, Anders ; Hausswolff, Annika von ; Männikkö, Esko ; Lehtola, Jouko ; Tunbjörk, Lars ; Cuenca Rasmussen, Lilibeth ; Harlev, Lise ; Gamdrup, Mads ; Kvium, Michael ; Bäckström, Miriam ; Johansson, Peter ; Rodland, Torbjorn
Deens
Exhibition. Anders Zorn og Nordisk Samtidskunst. Arken Museum for Moderne Kunst Ishoj, 26.06.2004 - 05.09.2004.
boek